A conceptual framework to integrate fault prediction sub-process for software product lines - Catal, Cagatay; Diri, Banu (IEEE COMPUTER SOC, 2008)
Software product line engineering is a growing recent paradigm to develop similar products using reusable core assets such as architecture and test cases. The general aim is to enhance quality and decrease development costs. Current software product line engineering frameworks apply. only a few quality assurance activities but today's single-system engineering has much more quality assurance activities that can be adapted to software product lines. In this study, software fault prediction sub-process is integrated into software product line engineering framework and the key activities are defined. This approach will improve quality and enhance testing process for software product lines.
Keywords: Computer Science